2023
DOI: 10.1186/s13244-023-01464-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of CT and MRI radiomics in ovarian cancer: methodological issues and clinical utility

Abstract: Objectives We aimed to present the state of the art of CT- and MRI-based radiomics in the context of ovarian cancer (OC), with a focus on the methodological quality of these studies and the clinical utility of these proposed radiomics models. Methods Original articles investigating radiomics in OC published in PubMed, Embase, Web of Science, and the Cochrane Library between January 1, 2002, and January 6, 2023, were extracted. The methodological qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Most published meta-analyses on the application of machine learning in ovarian cancer focus on the diagnosis and prediction of ovarian cancer; however, there are some differences in specific research methods, evaluation tools, and presentation of results. Huang et al [ 57 ] reviewed the application of computed tomography and magnetic resonance imaging radiomics in ovarian cancer, achieving promising results in differential diagnosis and prognosis prediction. Other studies [ 58 , 59 ] have summarized artificial intelligence methods for gynecological malignant tumors, emphasizing that variable selection, machine learning methods, and end point selection can all influence model performance.…”
Section: Discussionmentioning
confidence: 99%
“…Most published meta-analyses on the application of machine learning in ovarian cancer focus on the diagnosis and prediction of ovarian cancer; however, there are some differences in specific research methods, evaluation tools, and presentation of results. Huang et al [ 57 ] reviewed the application of computed tomography and magnetic resonance imaging radiomics in ovarian cancer, achieving promising results in differential diagnosis and prognosis prediction. Other studies [ 58 , 59 ] have summarized artificial intelligence methods for gynecological malignant tumors, emphasizing that variable selection, machine learning methods, and end point selection can all influence model performance.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a review focusing on ovarian imaging, which included 63 studies, found a median RQS of 6, corresponding to 30.6% of the total RQS, indicating lower scoring ( 53 ). Another meta-analysis covering 57 ovarian cancer studies reported an average RQS of 30.7%, which is also considered unsatisfactory ( 54 ). Reviews in other areas of radiomics, such as prostate cancer ( 55 ), meningiomas ( 56 ), nasopharyngeal carcinoma ( 57 ), and cardiovascular fields ( 58 ), have also highlighted concerns regarding the quality of machine learning and radiomics research, underscoring the general insufficiency in the scientific rigor of radiomics studies ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…The whole OC volume was assessed during texture analysis to differentiate epithelial OCs in previous studies [ 18 21 ]. However, no studies have investigated the potential of MRI texture analysis for discriminating CCC from EC [ 22 ].…”
Section: Introductionmentioning
confidence: 99%